THE INFLUENCE OF FINANCIAL PERFORMANCES ON INDONESIA’S STATE-OWNED BANKS TOWARDS SHARE RETURNS IN 2013-2016 - Sunarya, I Wayan (Jurnal Ekonomi & Studi Pembangunan, 2018)
The performance of financial statements shows the level of productivity in a company. Specific to banking sector, the performance of its financial statements can be analyzed from Economic Value Added (EVA) and Market Value Added (MVA). This study analyzes MVA and EVA are of state-owned banks consisting of Bank Tabungan Negara (BTN), Bank Negara Indonesia (BNI), Bank Mandiri and Bank Rakyat Indonesia (BRI). The results convey that Indonesiaâ€™s state-owned banks in giving share return to theirs shareholders are not influenced by Economic Value Added (EVA) and Market Value Added (MVA). There is an evidence that, EVA and MVA do not give any effect to share return because in the state owned bank in Indonesia, the investors have been very confident about the performance of banks in Indonesia so that without seeing the performance of the financial statements of investors have been very convinced from the fundamental point that the Indonesia state owned banks can bring benefits to investorsÂ